Excess winter mortality and morbidity before, during, and after the Great Recession: the Portuguese case - Almendra, Ricardo Jorge Meireles (2019)
Although winter mortality and morbidity are phenomena common to most European countries, their magnitude varies significantly from country to country. The geographical disparities among regions with similar climates are the result of several social, economic, demographic, and biological conditions that influence an individual's vulnerability to winter conditions. The impact of poor socioeconomic conditions may be of such magnitude that an economic recession may aggravate the seasonal mortality pattern. This paper aims to measure the seasonal winter mortality, morbidity, and their related costs during the Great Recession (2009-2012) in mainland Portugal and its Regional Health Administrations (RHAs) and to compare it with the periods preceding and following it. Monthly mortality and morbidity data were collected and clustered into three periods: Great Recession (2009-2012), Pre-Recession (2005-2008), and Post-Recession (2013-2016). The impact of seasonal winter mortality and morbidity during the Great Recession in Portugal and its Regional Health Administrations was measured through the assessment of age-standardized excess winter (EW) death and hospital admissions rate and index, expected life expectancy gains without EW deaths, EW rate of potential years of life lost, and EW rate of emergency hospital admission costs. Important increases of winter deaths and hospital admissions were identified, resulting in an important number of potential years of life lost (87 years of life lost per 100,000 inhabitants in 2009-2012), life expectancy loss (1 year in 2009-2012), and National Health Service costs with explicit temporal and spatial variations. These human and economic costs have decreased consistently during the analyzed periods, while no significant increase was found during the Great Recession. Despite its reduction, the winter excess morbidity and mortality highlight that Portugal still faces substantial challenges related to a highly vulnerable population, calling for investments in better social and health protection.